2009
DOI: 10.1097/tp.0b013e31818bbe06
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Intimal Thickening at Implantation Adversely Affects Long-Term Kidney Allograft Function

Abstract: Our data provide evidence that donor-related vasculopathy, at the time of transplantation, has a persistent significant impact on the subsequent graft function. This effect becomes only apparent at 1 year posttransplantation and is increased in recipients with inadequately controlled blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
2
9
2
1
Order By: Relevance
“…Previous reports have already demonstrated that organ quality at the time of donation is an important factor in determining allograft function after deceased-donor kidney transplantation [11]. Our present results showed that pre-existing mild fibrous intimal thickening in the grafts was associated with reduced allograft function, but not with renal function of the remnant donor kidney after donation.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Previous reports have already demonstrated that organ quality at the time of donation is an important factor in determining allograft function after deceased-donor kidney transplantation [11]. Our present results showed that pre-existing mild fibrous intimal thickening in the grafts was associated with reduced allograft function, but not with renal function of the remnant donor kidney after donation.…”
Section: Discussionsupporting
confidence: 73%
“…An interlobular artery was defined as a vascular structure comprised of two or three layers of myocytes in addition to an adventitial layer and an intimal layer. To evaluate the severity of arteriosclerotic vasculopathy, we quantitatively analyzed the intima-to-media ratio (I/M ratio), as previously described [11]. We defined non-arteriosclerotic lesions as lesions with an I/M ratio <25%, mild fibrous intimal thickening in the interlobular artery as an I/M ratio of 25–50% and severe fibrous intimal thickening in the interlobular artery as an I/M ratio >50%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, a previous study showed that allografts with pre-existing arteriosclerotic intimal thickening on preimplantation biopsies had lower function at 1 and 3 years after transplantation [19]. The reason for the discrepancy is unclear, but could be related to different methods for measuring intimal thickening or different patient characteristics such as recipient blood pressure which has been shown to influence the impact of pre-existing vasculopathy on graft function [20] or differences in immunosuppression. Future studies are needed to examine the interplay between donor kidney vascular disease, recipient vascular disease, and the immunosuppressive regimen in order to evaluate the relative impact of each on long-term allograft function.…”
Section: Discussioncontrasting
confidence: 40%